Serum Interleukin-15 Levels Are Associated with Severity of Pain in Patients with Knee Osteoarthritis - Sun, Jian-Min (Hindawi Publishing Corporation, 2013)
Background. Inflammation plays a crucial role in the development and progression of osteoarthritis (OA). Interleukin-15 (IL-15) is a well-known proinflammatory cytokine. Objective. We aimed at evaluating the relationship between serum IL-15 levels and the severity of pain as well as radiographic progression in patients with knee OA. Methods. Two hundred and twenty-six OA patients and 106 controls were enrolled in this study. The symptomatic/radiological severity of OA was assessed by the Western Ontario McMaster University Osteoarthritis Index- (WOMAC-)pain scores/Kellgren-Lawrence (KL) grading system. Serum IL-15 levels were measured by enzyme-linked immunosorbent assay (ELISA). Results. Serum IL-15 levels were significantly higher in OA patients compared with controls. Serum IL-15 levels were independently and positively correlated with WOMAC-pain scores but not KL grades in OA patients. Conclusions. We demonstrated that increased serum IL-15 levels were independently correlated with self-reported greater pain in knee OA patients. These results suggest that IL-15 might play a crucial role in the pathogenesis of OA related pain and therapeutic interventions by blocking IL-15 signaling pathways to delay the degenerative process of OA related pain which warrants further investigations.